PENGARUH PENGGUNAAN MEDIA PLASTISIN TERHADAP KEMAMPUAN MENGENAL ANGKA PADA ANAK USIA DINI - Ratna Ratna; Herlina Herlina; Muhammad Yusri Bachtiar; Wahira Wahira (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study aims to describe the ability to recognize numbers in early childhood and analyze the effect of the use of plasticine media on the improvement of these abilities. Early childhood is at a stage of cognitive development that requires concrete and interactive experiences in learning, so plasticine media is chosen as a tool to introduce numbers through play activities. The research method used is quantitative with a quasi-experimental design. Data were collected through observation and tests of the ability to recognize numbers before and after treatment. The results of the study show that the initial ability to recognize numbers in early childhood is at the basic level, namely being able to recognize the numbers 1-5. After the use of plasticine media, there was a significant improvement in the ability to recognize numbers, including understanding shapes, sequences, and number concepts. Children are more motivated and actively involved in learning. The conclusion is that plasticine media is effective in improving children's ability to recognize numbers and provide a concrete, fun learning experience according to the characteristics of early childhood development.